2020
DOI: 10.1177/2054358120962589
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives From an Onconephrology Interest Group: Conference Report

Abstract: Introduction and objective: Onconephrology is a new and evolving field that deals with kidney complications in patients with cancer as well as the management of cancer in patients with preexisting kidney disease. With increasing numbers of patients with cancer with kidney-related complications, the field has garnered increased attention. Thus, an annual Greater Toronto Area Onconephrology Interest Group symposium was held in May 2019. The objective of the meeting was to demonstrate the junctures between oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…AKI not only contributes to significant morbidity, but also increases the risk of progression to chronic kidney disease (CKD). It has been reported that 12% to 25% of patients with solid organ malignancies develop CKD [4,37]. The onset of either AKI or CKD in this patient population constitutes a critical clinical milestone that exacerbates both morbidity and mortality independently of the cancer's stage.…”
Section: Discussionmentioning
confidence: 99%
“…AKI not only contributes to significant morbidity, but also increases the risk of progression to chronic kidney disease (CKD). It has been reported that 12% to 25% of patients with solid organ malignancies develop CKD [4,37]. The onset of either AKI or CKD in this patient population constitutes a critical clinical milestone that exacerbates both morbidity and mortality independently of the cancer's stage.…”
Section: Discussionmentioning
confidence: 99%